Determinants of working adult' organic food purchase intention - Lee, Wan Qi (2023)
This research aims to examine the relationship between the five independent variables which are personal attitude, subjective norms, perceived behavioural control, electronic word-of-mouth (eWOM) and brand awareness towards organic food purchase intention of Malaysian working adults. The target respondents in this research are working adults aged 18 to 64 years old, who are currently working or employed, using snowball sampling method. Besides, an online questionnaire was used as the research instrument and 275 responses were collected while only 264 responses are valid. Data collected from the survey are analysed using Statistical Package for Social Science (SPSS) version 28. The responses were analysed using descriptive analysis, reliability analysis, normality test, Pearson correlation and multiple regression analysis and presented through tables and figures format. The research findings show that personal attitude,perceived behavioural control, electronic word-of-mouth (eWOM) and brand awareness have significant relationship with working adults’ purchase intention of organic food, while subjective norms do not. In addition, this research includes managerial implications for marketers or companies of the organic food industry,offering valuable insights to guide their decision-making processes. Lastly, the research identifies and addresses the limitations associated with this research, providing recommendations for future researchers to effectively manage these limitations.